Strategi Pemasaran dalam Meningkatkan Omzet Rumah Makan Pelangi Kabupaten Wakatobi Menurut Perspektif Ekonomi Syariah - Rizki Nur Wakhid Hidayatullah; Sitti Rahma Guruddin (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2022)
Marketing activities must be carried out by all companies, especially companies that seek turnover or profit, such as restaurant companies. The Prophet Muhammad taught his people how to trade and do proper marketing. Competition is common in every business that is done. Pelangi Restaurant also has competitors in accordance with their fields. Pelangi Restaurant needs several strategies to remain competitive with other restaurants by implementing healthy competition guidelines. The aims of this study were (1) to find out the marketing strategy for the Pelangi Restaurant in Wakatobi district. (2) To find out the increase in turnover of the Pelangi Restaurant in Wakatobi district. (3) To find out the marketing strategy in increasing turnover of Pelangi Restaurant Wakatobi district According to the Sharia Economic Perspective. This type of research is a qualitative descriptive research with the method (field research), namely research that takes place related to the object under study. In this case the data analysis used by the author is descriptive qualitative, namely an analysis that describes the situation or status of the phenomenon in words or sentences, then separated according to the categories to obtain conclusions. Research results: (1) The marketing strategy implemented by Rumah Makan Pelangi Wakatobi District applies a marketing mix strategy. (2) Marketing mix strategy, supporting and inhibiting factors were found in efforts to increase turnover at Pelangi Restaurant. (3) The marketing strategy in increasing the turnover of Rumah Makan Pelangi shows good results because it applies elements of Islamic Economics (Rabbaniyah) which assumes that every human movement is always supervised by Allah SWT.